PENDIDIKAN ISLAM DI ZAMAN KEMAJUAN DALAM TINJAUAN SEJARAH PERADABAN ISLAM - Muhammad Sarib Abdul Rasak (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Islamic education is always changing from time to time, one of the important things to analyze is Islamic education in the period of progress in the era of the Abbasid dynasty. History records that the journey of Islamic education had progressed so rapidly, far behind Western education. However, later it experienced a setback and was inversely proportional to Western education which continued to soar far ahead of leaving Islamic education until now. Therefore, it is important to reflect on the glorious history of Islamic education or what is called the era of progress in Islamic education. Studying and understanding things that promote Islamic education in the age of progress, as an effort to build Islamic education in the future. Thus, based on the explanation that has been described, the formulation of the problem to be solved in this study is related to the description of Islamic education in the era of progress, in this study, namely library research, namely the type of research conducted by reading books or magazines and other data sources to collect data. data from various literature, both libraries and in other places. History records Islamic education in the Abbasid era as a period of progress and glory of Islamic education. The caliph as the holder of the power is a figure who is so strong and loves science very much. The seven caliphs who were known to love the development of science were al-Mahdi, al-Hadi, Harun al-Rashid, al-Ma'mun, al-Mu'tashim, al-Wasiq, and al-Mutawakkil. The rapid development of science was centered in Baghdad and lasted for approximately five centuries (750 AD - 1258 AD). Throughout the Abbasid Caliphate, many well-known educational institutions have been built, one of which is Baitul Hikmah. During the Abbasid era, the Nizamiyah Madrasah educational institution appeared for the first time and was the forerunner to the development of Madrasah in today's modern era.